Pulmonary and skin evaporative heat loss during exercise in hot dry conditions in crossbreds - UPADHYAY, R C; AGGARWAL, ANJULI (The Indian Journal of Animal Sciences, 2013)
Six apparently healthy male calves (Tharparkar X Holstein) were subjected to treadmill exercise for 1 hr in hot dry conditions. Exercise during heat increased heat loss by evaporation through sweating and through pulmonary system. Before exercise heat loss through skin was 87% and through pulmonary system was 12%. After exercise 88% of the heat was lost by sweating and 11 % by pulmonary system. High level of evaporation from the skin reduced the demand for evaporative heat loss from respiratory tract particularly during exercise under heat stress. Increase in alveolar ventilation and increase in oxygen consumption were related.